Zdolności dyskryminacyjne wskaźników finansowych w ocenie kondycji finansowej podmiotów gospodarczych - Wójciak, Mirosław; Wójcicka, Aleksandra (The Discriminative Ability of Financial Ratios to Estimate the Credit Risk Level, 2008)
The paper is an attempt to select those financial ratios which in the construction and electromachine sector of Polish economy would be the best to predict the approaching financial problems of a company. The paper compares the classification results of quoted companies due to the level of their credit risk and the discriminative abilities of particular financial ratios. The authors tried to point die levels and limits of ratios correlated with different levels of default risk. The appointed ratios be used in traditional credit risk models and consequently they allow for generalising the optionpricing model to unquoted companies. An another attempt is to examine the ratio limits in the economic growth and recession time.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 173-181